2021
DOI: 10.1111/exd.14466
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of YAP/TAZ alters the biological behaviours of keloid fibroblasts

Abstract: Abnormal activation of fibroblasts plays a crucial role in keloid development. However, the mechanism of fibroblast activation remains to be determined. YAP/TAZ are key molecules in the Hippo signalling pathway that promote cell proliferation and inhibit apoptosis. Here, we show that keloid fibroblasts have higher levels of YAP/TAZ mRNA and proteins on primary culture. Targeted knockdown of endogenous YAP or TAZ significantly inhibited cell proliferation, reduced cell migration, induced cell apoptosis and down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…Mechanical transduction of YAP/TAZ is mainly controlled by its subcellular localization because YAP/TAZ activation requires its accumulation in the nucleus ( Panciera et al, 2017 ). Gao et al (2022 ) study showed that increased nuclear YAP/TAZ staining was observed in keloid tissue fibroblasts compared with that in normal skin. Activation of YAP-TAZ in the nucleus leads to the expression of pro-fibrosis genes, increased α-SMA expression, and excessive matrix deposition ( Panciera et al, 2017 ).…”
Section: Biomechanical Factors and Mechanotransduction Pathways In Ke...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical transduction of YAP/TAZ is mainly controlled by its subcellular localization because YAP/TAZ activation requires its accumulation in the nucleus ( Panciera et al, 2017 ). Gao et al (2022 ) study showed that increased nuclear YAP/TAZ staining was observed in keloid tissue fibroblasts compared with that in normal skin. Activation of YAP-TAZ in the nucleus leads to the expression of pro-fibrosis genes, increased α-SMA expression, and excessive matrix deposition ( Panciera et al, 2017 ).…”
Section: Biomechanical Factors and Mechanotransduction Pathways In Ke...mentioning
confidence: 99%
“…Gao et al have significantly inhibited the proliferation of keloid fibroblasts, reduced cell migration, induced apoptosis, and down-regulated collagen I production by targeting low endogenous YAP or TAZ knockdown. YAP/TAZ inhibitor verteporfin has shown similar but stronger inhibitory effect on fibroblasts ( Gao et al, 2022 ).…”
Section: Clinical Control Of Skin Tension For Keloid Prevention and T...mentioning
confidence: 99%
“…Besides, conditional YAP/TAZ knockout in the dermis or application of interfering RNAs to the wound site leads to delayed wound closure due to decreased cell proliferation, indicating that YAP/TAZ promotes wound healing (79). Gao et al found that human keloid fibroblasts have higher YAP/TAZ mRNA and protein levels than normal skin tissue on primary culture (80). Additionally, knockdown of YAP/TAZ with siRNA interference technique or usage of verteporfin significantly reduced proliferation, migration, survival and collagen production of human keloid fibroblasts (Figure 4C), indicating that YAP/TAZ inhibitor had potential clinical significance for HTS management (80).…”
Section: Yap/tazmentioning
confidence: 99%
“…(b) Quantification of wound healing rates at each stage in control versus dKO animals ( 79 ). (C) (a) (Left) Human keloid fibroblasts (HKFs) had increased metabolic activity demonstrated by high RLU value than human normal fibroblasts (HNFs) (n = 3) ( 80 ). (Right) Knockdown of YAP or TAZ and verteporfin treatment decreased cell metabolic activity in both HNFs and HKFs (n = 3) ( 80 ).…”
Section: Mechanical Forces and Hts Formationmentioning
confidence: 99%
See 1 more Smart Citation